Adaptasi Sosial dan Budaya Mahasiswa Asing di Indonesia: Pengaruh Budaya Jawa dalam Program Bahasa Indonesia bagi Penutur Asing (BIPA) - Kundharu Saddhono; Muhammad Rohmadi; Ani Rakhmawati; Suhailee Sohnui (Society, 2025)
The Indonesian Language Program for Foreign Speakers (BIPA) is increasingly in demand among international students studying Indonesian. This study aims to investigate the cultural and social changes experienced by these students by focusing on the influence of Javanese culture. The study employed a descriptive qualitative ethnographic approach and was conducted in Central Java, East Java, and Yogyakarta. Data were collected from documents and informants. The results indicate that Javanese culture influences the cultural and social changes of foreign students in Indonesia, as they become more enthusiastic and active. In addition, their internal and external adaptation helps them better understand the Indonesian language and culture.